2020
DOI: 10.37506/mlu.v20i4.1925
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Age on Intracytoplasmic Sperm Injection (ICSI) Outcomes in Infertile Couples

Abstract: Objective:The aim of the study is to investigate the impact of maternal age on ICSI outcomes represented by the number of retrieved oocytes, number of fertilized oocytes, embryo quality and pregnancy rate in infertile couples undergoing ICSI. Patients and Method:The study included sixty two infertile couples who underwent ICSI cycles. They divided in to two groups depending on females' age: group Ι with age less than 35 years and group ΙΙ with age more than 35 years. Assessment of ICSI outcomes in form of retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Our study showed a significant negative correlation between maternal age and the number of collected mature oocytes (MII). This finding agrees with previous studies that mentioned a significant reduction in the number and quality of collected oocytes with increased age of the female partner (20,21). However, the level of 8-OHdG in our study had significant negative correlation with the number of mature oocytes from one side and in significant positive correlation with increased maternal age on the other side, so this could be an explination why is the negative impact of maternal age on the quality and number of the oocyte.…”
Section: Discussionsupporting
confidence: 94%
“…Our study showed a significant negative correlation between maternal age and the number of collected mature oocytes (MII). This finding agrees with previous studies that mentioned a significant reduction in the number and quality of collected oocytes with increased age of the female partner (20,21). However, the level of 8-OHdG in our study had significant negative correlation with the number of mature oocytes from one side and in significant positive correlation with increased maternal age on the other side, so this could be an explination why is the negative impact of maternal age on the quality and number of the oocyte.…”
Section: Discussionsupporting
confidence: 94%
“…The loss of mitochondrial activity in oocytes obtained from AMA women undergoing IVF could lead to slower cell divisions that affect embryonic development and impair pregnancy rates [46]. Embryos produced from these oocytes are usually of poor quality and exhibit lower implantation potential [47]. This study found no significant difference in embryo quality between older and younger patients, but a statistical difference in the number of developed embryos was detected between younger and older age groups.…”
Section: Discussionmentioning
confidence: 49%